Surgical options after Fontan failure. Issue 14 (13th April 2016) - van Melle, Joost P; Wolff, Djoeke; Hörer, Jürgen; Belli, Emre; Meyns, Bart; Padalino, Massimo; Lindberg, Harald; Jacobs, Jeffrey P; Mattila, Ilkka P; Berggren, Håkan; Berger, Rolf M F; Prêtre, Rene; et al.
Abstract : Objective: The objective of this European multicenter study was to report surgical outcomes of Fontan takedown, Fontan conversion and heart transplantation (HTX) for failing Fontan patients in terms of all-cause mortality and (re-)HTX. Methods: A retrospective international study was conducted by the European Congenital Heart Surgeons Association among 22 member centres. Outcome of surgery to address failing Fontan was collected in 225 patients among which were patients with Fontan takedown (n=38; 17%), Fontan conversion (n=137; 61%) or HTX (n=50; 22%). Results: The most prevalent indication for failing Fontan surgery was arrhythmia (43.6%), but indications differed across the surgical groups (p<0.001). Fontan takedown was mostly performed in the early postoperative phase after Fontan completion, while Fontan conversion and HTX were mainly treatment options for late failure. Early (30 days) mortality was high for Fontan takedown (ie, 26%). Median follow-up was 5.9 years (range 0–23.7 years). The combined end point mortality/HTX was reached in 44.7% of the Fontan takedown patients, in 26.3% of the Fontan conversion patients and in 34.0% of the HTX patients, respectively (log rank p=0.08). Survival analysis showed no difference between Fontan conversion and HTX (p=0.13), but their ventricular function differed significantly. In patients who underwent Fontan conversion or HTX ventricular systolic dysfunction appeared to be the strongest predictor of mortality or (re-)HTX. Patients with valveless atriopulmonary connection (APC) take more advantage of Fontan conversion than patients with a valve-containing APC (p=0.04). Conclusions: Takedown surgery for failing Fontan is mostly performed in the early postoperative phase, with a high risk of mortality. There is no difference in survival after Fontan conversion or HTX.